Inborn errors of immunity underlying a susceptibility to pyogenic infections: from innate immune system deficiency to complex phenotypes. (November 2022) - Conti, Francesca; Marzollo, Antonio; Moratti, Mattia; Lodi, Lorenzo; Ricci, Silvia
Abstract: Background: Pyogenic bacteria are associated with a wide range of clinical manifestations, ranging from common and relatively mild respiratory and cutaneous infections to life-threatening localized or systemic infections, such as sepsis and profound abscesses. Despite vaccination and the widespread use of effective antibiotic treatment, severe infection is still observed in a subset of affected patients. Objectives: We aim to summarize the available data regarding inborn errors of immunity that result in a high risk of severe pyogenic infections. Sources: Case series, as well as review and original articles on human genetic susceptibility to pyogenic infections were examined. Content: We review host-associated factors resulting in inborn errors of immunity and leading to a susceptibility to pyogenic infections, including deficiency in major components of the immune system (e.g., neutrophils, complement, immunoglobulin, and spleen function) and novel monogenic disorders resulting in specific susceptibility to pyogenic infection. Specifically, innate immune system deficiency involving toll-like receptors and associated signaling typically predispose to a narrow spectrum of bacterial diseases in otherwise healthy people, making a diagnosis more difficult to suspect and confirm. More complex syndromes, such as hyper IgE syndrome, are associated with a high risk of pyogenic infections due to an impairment of the interleukin-6 or -17 signaling, demonstrating the pivotal role of these pathways in controlling bacterial infections. Implications: In clinical practice, awareness of such conditions is essential, especially in the pediatric setting, to avoid a potentially fatal diagnostic delay, set the most proper and prompt treatment, and ensure prevention of severe complications.